2011
DOI: 10.1016/j.anifeedsci.2011.04.096
|View full text |Cite
|
Sign up to set email alerts
|

A novel method to determine simultaneously methane production during in vitro gas production using fully automated equipment

Abstract: a b s t r a c tAn adaptation of fully automated gas production equipment was tested for its ability to simultaneously measure methane and total gas. The simultaneous measurement of gas production and gas composition was not possible using fully automated equipment, as the bottles should be kept closed during the incubations. A separate small opening with a screw cap and septum was made in each bottle, making it possible to take very small aliquots (10 l) from the gas in the headspace with a syringe for immedia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
84
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(87 citation statements)
references
References 25 publications
0
84
1
2
Order By: Relevance
“…This reduction occurred with a concomitant decrease in total VFA production, an indication of an inhibition of feed digestion. In a previous in vitro study by Pellikaan et al (2011), CH 4 production was almost completely inhibited (~100% reduction) during the first 30 h of 72 h incubation when CDH (2.5 mg/ml) was added to soybean hulls or corn. Interesting, in the study of Pellikaan et al (2011), the extent of decrease of CH 4 production from soybean hulls was only 65% after 72 h incubation, suggesting a possible adaptation of rumen microbes to CDH exposure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This reduction occurred with a concomitant decrease in total VFA production, an indication of an inhibition of feed digestion. In a previous in vitro study by Pellikaan et al (2011), CH 4 production was almost completely inhibited (~100% reduction) during the first 30 h of 72 h incubation when CDH (2.5 mg/ml) was added to soybean hulls or corn. Interesting, in the study of Pellikaan et al (2011), the extent of decrease of CH 4 production from soybean hulls was only 65% after 72 h incubation, suggesting a possible adaptation of rumen microbes to CDH exposure.…”
Section: Resultsmentioning
confidence: 99%
“…In a previous in vitro study by Pellikaan et al (2011), CH 4 production was almost completely inhibited (~100% reduction) during the first 30 h of 72 h incubation when CDH (2.5 mg/ml) was added to soybean hulls or corn. Interesting, in the study of Pellikaan et al (2011), the extent of decrease of CH 4 production from soybean hulls was only 65% after 72 h incubation, suggesting a possible adaptation of rumen microbes to CDH exposure. Adaptation of rumen microbes to essential oils was previously reported in continuous-culture studies (Cardozo et al, 2004;Busquet et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…In certain instances a substrate by additive interaction has been observed. Pellikaan et al (2011) reported a complete inhibition of CH 4 production during the first 30 h of incubation, irrespective of substrate composition (soyhulls or maize), with bromoethanesulphonate (BES) and cinnamaldehyde. However, CH 4 production from soybean hulls with BES or cinnamaldehyde was 65% lower compared with soyhulls without additive after 72 h, suggesting an influence on adaptation, whereas no CH 4 was produced after 72 h production when maize was incubated with these additives.…”
Section: Substrate and Incubation Buffer 341 Substratementioning
confidence: 99%
“…Machmüller et al (2001) investigated effects of medium chain fatty acids in incubations containing high or low amounts of fiber. The efficacy of monensin has been examined using corn meal or timothy hay (Russell and Strobel, 1988) and corn meal or soyabean hulls (Pellikaan et al, 2011) as substrates. In certain instances a substrate by additive interaction has been observed.…”
Section: Substrate and Incubation Buffer 341 Substratementioning
confidence: 99%
See 1 more Smart Citation